2008
DOI: 10.1210/jc.2007-1029
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the IDE-KIF11-HHEX Gene Locus Are Reproducibly Associated with Type 2 Diabetes in a Japanese Population

Abstract: Polymorphisms in the IDE-KIF11-HHEX gene locus are associated with susceptibility to type 2 diabetes across the boundary of race.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 20 publications
3
23
0
1
Order By: Relevance
“…The rs13266634, rs10811661 and rs2237892 risk alleles were major alleles, while the other risk alleles were minor alleles in our population, consistent with previous reports in European populations (Scott et al 2007;Saxena et al 2007;Zeggini et al 2007). Interestingly, the G allele of rs1111875, which was reported to be a major allele in Caucasian ethnic groups, was revealed as a minor allele in our study; this is supported by similar results from Japanese populations (Furukawa et al 2008;Horikoshi et al 2007;Omori et al 2008).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The rs13266634, rs10811661 and rs2237892 risk alleles were major alleles, while the other risk alleles were minor alleles in our population, consistent with previous reports in European populations (Scott et al 2007;Saxena et al 2007;Zeggini et al 2007). Interestingly, the G allele of rs1111875, which was reported to be a major allele in Caucasian ethnic groups, was revealed as a minor allele in our study; this is supported by similar results from Japanese populations (Furukawa et al 2008;Horikoshi et al 2007;Omori et al 2008).…”
Section: Resultssupporting
confidence: 91%
“…In our study, each SNP in the HHEX, CDKN2A/B, CDKAL1 and KCNQ1 genes showed a significant association with T2DM. The adjusted allele-specific OR value of rs1111875 (1.43) was similar to that of Japanese groups (1.30-1.42) (Furukawa et al 2008;Horikoshi et al 2007;Omori et al 2008), but higher than that reported from white populations (1.10-1.15) (Saxena et al 2007;Scott et al 2007;Sladek et al 2007). The HHEX gene product is known to act as both a transcription activator and repressor required for the development of the pancreas, liver and blood vessels and is also a target of the Wnt/b-catenin signaling pathway (McLin et al 2007;Foley and Mercola 2005).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In addition, Japanese research groups, including ours, recently identified an association of the potassium voltage-gated channel KQT-like subfamily member 1 (KCNQ1) locus with type 2 diabetes in populations of East Asian descent [8,9]. Because most of these loci have also been shown to be associated with type 2 diabetes in other ethnic populations [8][9][10][11][12][13], these loci could be considered as convincing susceptibility genes for type 2 diabetes across different ethnicities.…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3][4][5] TCF7L2, CDKAL1, CDKN2A/B, IGF2BP2, SLC30A8 and HHEX have been widely replicated as susceptibility genes for type 2 diabetes in Asian populations [6][7][8][9][10][11][12] as well as in populations of European ancestry. 13,14 We recently identified KCNQ1 as a novel susceptibility gene, as well as seven other candidate susceptibility loci in a multistage GWAS for type 2 diabetes in the Japanese population, in which a total of 1612 cases and 1424 controls and 100 000 single nucleotide polymorphisms (SNPs) were included.…”
Section: Introductionmentioning
confidence: 99%